Bringing new focus on groundwater irrigation in Nepal’s irrigation policy: Potential policy opportunities and pathways - Chakraborty, Shreya; Neupane, Nilhari; Karki, Shanta; Krupnik, Timothy J. (TAFSSA, 2023)
The last irrigation policy of Nepal (2003) acknowledged that the traditional focus of irrigation development in Nepal has been on run-off river-based surface water irrigation. To counter the problems of seasonal low flows of rivers, groundwater resources were regarded mostly as a supplementary or conjunctive irrigation source that could extend irrigation year-round. However, there have been several new developments in the irrigation sector and water systems of Nepal that now call for a new focus and approach to groundwater irrigation